A Comparison of the Authoritarian Strategies Used by Brazil and Turkey to Tackle the COVID-19 Crisis - Kisa, Adnan (Journal of Applied Business and Economics, 2023)
For authoritarian-minded leaders, the COVID-19 crisis offered a convenient pretext to silence critics and consolidate power. Populist and autocratic leaders used the crisis as an excuse to do things they had long planned to do but had not been able to. Using a narrative literature review, this study examines the authoritarian responses to COVID-19 in Brazil and Turkey between 2020 and 2021. Available articles were retrieved from Medline and Google Scholar using a non-systematic approach using inclusion and exclusion criteria. Major identified authoritarian responses were imprisoning human rights defenders, journalists, lawyers, political activists, and medical professionals; flaunting public health and human rights laws; blaming other countries for causing the pandemic; and underreporting COVID cases. The study concludes that these actions had devastating consequences for democracy, human rights, and public health.